The Government and the News-Print Paper Manufacturers - Merchant, E. O. (Quarterly Journal of Economics, 1920)
I. Introduction: review of 1916–17, 313. — II. The events of 1918–19, 314. — Federal Trade Commission's award, 315. — Commission's supplemental award, approved by Circuit Court, 316. — III. Character of evidence, 317. — IV. Cost of manufacture, 318. — V. Investment, 322. — VI. Rate of profit on investment, 325. — VII. Results of Price Fixing, 326. — Difference in the awards of the Commission and Circuit Judges, 327. — Victory for Manufacturers, 328. — Conclusion, 328.